EVOLUTIONARY PROCESSES OF THE FAMILY SYSTEM - Arapbaeva Damegul Kurbanovna (Zeta Repository, 2023)
This article analyzes the evolutionary processes of the family system: family myth,family history, concepts of the family life cycle. Also, the article covers the basis of family life: family norms and rules, family values, family traditions and rituals.